Dinamika Dukungan Sosial Keluarga dan Gratitude pada Perempuan Penderita Kanker - Mariyani, Devi; Nurhayati, Siti Rohmah (Universitas Negeri Makassar, 2024)
This research aims to look at family social support and gratitude given by families to women who are battling cancer. There were 3 informants in this study, namely, women aged 40 years and over who were patients of YKI (Indonesian Cancer Foundation) DIY Coordinator Branch. The method used in this research is qualitative using a phenomenological approach. The data collection technique used in this research was interviews. The research results show that there is family social support and gratitude for the three subjects. Based on the results of research conducted, it is known that social support, especially family, can improve the health and quality of life of cancer patients. Gratitude makes them have a more positive attitude towards the cancer they suffer from. With gratitude, informants can view and interpret their lives more easily. There are positive benefits that can be obtained when cancer patients apply gratitude to themselves, individuals will feel better in responding or responding to every event in their life.